Refugia som metod för att minska utvecklingen av anthelmintikaresistens hos får - Leijonflycht, Carolina (2011)
Anthelmintic resistance is a major problem in sheep husbandry all over the world. One way to slow down the development of anthelmintic resistance is to keep part of the parasite population in refugia (unexposed to drugs) which will maintain the genes for susceptibility within the population. Climate, type of parasite and drenching regimes effect the size of the refugia. Dilution of resistant with susceptible parasites, targeted treatment and targeted selective treatment are all management strategies that employ refugia. Dilution is possible but complicated. Targeted treatment means not drenching when there are few parasites in refugia as this selects for resistance. Targeted selective treatment means only drenching animals that need treatment. FAMACHA© has turned out to be an effective method to pick out the animals which suffer from an infection with H. contortus. To use daily weight gain as an indicator of which animals to treat is effective but costly. Five point check© needs development and evaluation to be a useful alternative. The methods need to be simple, cheap and functional in order to be used by farmers. There is also a need for foregoers among the farmers that can show the others that the new methods work and do not lead to production loss and a worsened animal health. Refugia delay the development of anthelmintic resistance – it does not stop it.